Carte physique et politique de l'AmeÌrique du Nord. - Drioux, abbeÌ (Claude-Joseph), 1820-1898 (EugeÌ€ne Belin, 1865)
Map shows British America, Mexico, the United States, the West Indies, and Central America; some state and territorial boundaries; major cities, Gulf Stream and equatorial current; Indian Territory, territories of Nebraska, Washington, Oregon, Utah, New Mexico, Kansas, Arizona, and Minnesota; areas of Native American habitation; Alaska as "ReÌgion du Nord-ouest (Aux Etats-Unis)." Includes key to numbered states. Insets: "TraceÌ des voyages de Christophe Colomb" [Trace the voyages of Christopher Columbus] and "SuppleÌment pour le Mexique" [Supplement for Mexico]. Relief shown by hachures and spot heights. Scale not given.